2016
DOI: 10.1007/s10661-016-5420-2
|View full text |Cite
|
Sign up to set email alerts
|

Response of macrophyte communities to flow regulation in mountain streams

Abstract: River macrophytes are widely used in freshwater ecosystem assessment because of their sensitivity to anthropogenic pressures, even if there are only a few studies that investigated how macrophytes respond to water regime alterations. In this study, we analyzed the effects of dams on river macrophyte communities through a comparison between upstream and downstream sides from 18 dams located in Alps and Apennines. A co-inertia analysis and a Mantel test were applied to assess if the analysis of environmental par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
(53 reference statements)
0
16
0
1
Order By: Relevance
“…Discontinuities in community composition have been associated with dams, with assemblages exhibiting a shift from a composition similar to the drifting hydrochorous propagule bank upstream, to communities derived from local seed‐bearing plants downstream (Andersson et al, ; Jansson, Nilsson, Dynesius, et al, ). Decreases in macrophyte diversity and abundance have been reported downstream of dams (Casado, García de Jalon, Delolmo, Barcelo, & Menes, ; García de Jalon, Sanchez, & Camargo, ), while in other cases an increase in macrophyte abundance has been reported (Abati, Minciardi, Ciadamidaro, Fattorini, & Ceschin, ; Goes, ; Tena, Vericat, Gonzalo, & Batalla, ), although in these studies, changes in macrophyte population structure were not directly linked to disruptions of hydrochory, and probably related to differences in hydrological regime. However, other studies have found evidence that the richness of riverine plant communities was linked to hydrochorous seed input, with free‐flowing rivers showing higher richness (Merritt, Nilsson, & Jansson, ; Nilsson, Ekblad, et al, ; Nilsson, Gardfjell, et al, ).…”
Section: Barrier Impacts On Macrophytesmentioning
confidence: 77%
See 1 more Smart Citation
“…Discontinuities in community composition have been associated with dams, with assemblages exhibiting a shift from a composition similar to the drifting hydrochorous propagule bank upstream, to communities derived from local seed‐bearing plants downstream (Andersson et al, ; Jansson, Nilsson, Dynesius, et al, ). Decreases in macrophyte diversity and abundance have been reported downstream of dams (Casado, García de Jalon, Delolmo, Barcelo, & Menes, ; García de Jalon, Sanchez, & Camargo, ), while in other cases an increase in macrophyte abundance has been reported (Abati, Minciardi, Ciadamidaro, Fattorini, & Ceschin, ; Goes, ; Tena, Vericat, Gonzalo, & Batalla, ), although in these studies, changes in macrophyte population structure were not directly linked to disruptions of hydrochory, and probably related to differences in hydrological regime. However, other studies have found evidence that the richness of riverine plant communities was linked to hydrochorous seed input, with free‐flowing rivers showing higher richness (Merritt, Nilsson, & Jansson, ; Nilsson, Ekblad, et al, ; Nilsson, Gardfjell, et al, ).…”
Section: Barrier Impacts On Macrophytesmentioning
confidence: 77%
“…Many of the observed changes in macrophyte community have been associated with the hydrological effects of dams, rather than their role in disrupting hydrochory. Stable flow conditions often found downstream of dams can increase aquatic plant cover in affected reaches (Abati et al, ; Goes, ; Ibáñez, Caiola, Rovira, & Real, ). Moderate disturbance caused by hydropeaking (frequent, short duration, artificial flow events) can also lead to increased macrophyte richness and abundance, compared to unregulated rivers (Bernez, Daniel, Haury, & Ferreira, ; Bernez, Haury, & Ferreira, ).…”
Section: Barrier Impacts On Macrophytesmentioning
confidence: 99%
“…Despite this, at national level a remarkable revival of interest in aquatic flora was stimulated by the enactment of the WFD ( Bolpagni et al, 2017a ). It has resulted into a renewed attention for inland aquatic habitats in general, and it has favored the integration of the available aquatic plant knowledge ( Testi et al, 2009 ; Ceschin et al, 2010 ; Azzella et al, 2013 , 2014 ; Villa et al, 2015 ; Abati et al, 2016 ; Bolpagni et al, 2016 ). Nevertheless, much work has to be done in order to facilitate the comparison and sharing of information gathered by the various institutional actors involved in the monitoring programs.…”
Section: Discussionmentioning
confidence: 99%
“…However, Szoszkiewicz et al () also report that although macrophyte metrics developed to indicate ecological status respond strongly to total phosphorus concentrations in terms of nutrient response in both rivers and lakes, substrate was most important in structuring macrophyte species composition and abundance in rivers. Many widely used metrics including the Macrophyte Biological Index for Rivers, the Macrophyte Index for Rivers, the River Nutrient Macrophyte Index, and the Reference Index respond negatively to increased shading by the tree canopy (Wiegleb, Gebler, van de Weyer, & Birk, ), but macrophyte communities also respond strongly to changes in hydrological and morphological parameters (Abati, Minciardi, Ciadamidaro, Fattorini, & Ceschin, ; Ceschin, Tombolini, Abati, & Zuccarello, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many widely used metrics including the Macrophyte Biological Index for Rivers, the Macrophyte Index for Rivers, the River Nutrient Macrophyte Index, and the Reference Index respond negatively to increased shading by the tree canopy (Wiegleb, Gebler, van de Weyer, & Birk, 2016), but macrophyte communities also respond strongly to changes in hydrological and morphological parameters (Abati, Minciardi, Ciadamidaro, Fattorini, & Ceschin, 2016;Ceschin, Tombolini, Abati, & Zuccarello, 2015).…”
Section: Introductionmentioning
confidence: 99%